2019
DOI: 10.1002/ente.201900975
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3‐Atomic Layer Deposited Films on CH3NH3PbI3: Intrinsic Defects and Passivation Mechanisms

Abstract: The initial interaction of atomic layer deposited films of Al2O3 at room temperature on CH3NH3PbI3 (MAPI) films is studied. Synchrotron radiation–based photoelectron spectroscopy is applied to analyze the initial changes in the Al‐derived features by comparing samples with different Al2O3 film thicknesses. It is found that polarons and excitons, both intrinsic defects of Al2O3, play a key role in the interface formation. The polaronic states uptake a charge from the MAPI substrate. This charge is transferred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…27 A similar behavior was reported by Yu et al 29 Synchrotron XPS analysis was employed by Kot et al, 30 which indicated that the interaction of ALD precursors occurs only at the surface of the CH 3 NH 3 PbI 3 and FA 0.85 MA 0.15 Pb(Br 0.15 I 0.85 ) 3 perovskite (where FA corresponds to the formamidinium cation) during the growth of Al 2 O 3 at room temperature. 23,24 In parallel, they showed that there is covalent bonding at the CH 3 NH 3 PbI 3 /Al 2 O 3 interface. At the same time, they identified a charge balance between the polaronic and excitonic states in CH 3 NH 3 PbI 3 and Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…27 A similar behavior was reported by Yu et al 29 Synchrotron XPS analysis was employed by Kot et al, 30 which indicated that the interaction of ALD precursors occurs only at the surface of the CH 3 NH 3 PbI 3 and FA 0.85 MA 0.15 Pb(Br 0.15 I 0.85 ) 3 perovskite (where FA corresponds to the formamidinium cation) during the growth of Al 2 O 3 at room temperature. 23,24 In parallel, they showed that there is covalent bonding at the CH 3 NH 3 PbI 3 /Al 2 O 3 interface. At the same time, they identified a charge balance between the polaronic and excitonic states in CH 3 NH 3 PbI 3 and Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 97%
“…So far, Al 2 O 3 is considered the only successful case of direct ALD processing on the perovskite absorber. 12,[23][24][25] A recent work from our group using infrared (IR) and x-ray photoelectron spectroscopy (XPS) analysis revealed that the interaction between H 2 O (used as coreactant) and CH 3 NH 3 PbI 3−x Cl x was negligible under the conditions adopted in the ALD recipe. 26 On the contrary, exposure to trimethylaluminum (TMA, used as metal precursor) was found to degrade the perovskite surface, leading to the effusion of methylammonium (MA) cations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] The electronic and chemical properties of the film in the bulk and at interfaces in the PSCs are often studied directly using various microscopic and spectroscopic methods. [ 5,6 ] In particular, time of flight secondary ion mass spectroscopy (ToF‐SIMS), transmission electron microscopy (TEM) [ 7–10 ] and field emission secondary electron microscopy (FESEM) [ 11 ] are used. The distribution of organic and inorganic cations has been determined over the whole thickness of the mixed cation‐based PSCs using ToF‐SIMS.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Moreover, Schmeißer and co-workers found that polarons and excitons, both intrinsic defects of Al 2 O 3 , easily bond to the perovskite crystalline surface by the covalent and ionic bond, of which the interaction between Al 2 O 3 and perovskite is of benefit for electron extraction. [28,29] Yang and co-workers used the thin Al 2 O 3 film to encapsulate PSCs to efficiently enhance the long-term stability for 2100 h under 80% relative humidity and at 30 C. [30] Apart from the ETL/perovskite and perovskite/HTL interfaces, the ITO/ETL interface also shows a remarkable impact on the electron extraction efficiency of conventional PSCs. The surface defects and micropores at the interface would retard the charge extraction, consequently increasing nonradiative recombination and enlarging the hysteresis phenomenon.…”
Section: Introductionmentioning
confidence: 99%